Resistance of blended concrete containing an industrial petrochemical residue to chloride ion penetration and carbonation (2014)
In this study, the resistance of blended concrete containing catalytic cracking residue (FCC) to chloride ion penetration and carbonation was examined. FCC was added at the levels of 10%, 20%, and 30% as partial replacement for cement. Concretes with 10% of silica fume (SF), 10% of metakaolin (MK), and without additives were evaluated as reference materials. The rapid chloride permeability test (RCPT) performed according to ASTM C1202 standards and an accelerated carbonation test in a climatic chamber under controlled conditions (23 °C, 60% RH and 4.0% CO2), were used in order to evaluate the performance of these concretes. Additionally, their compressive strength was determined. The results indicate that binary blends with 10% FCC had similar compressive strength to concrete without additives and had lower chloride permeability. 10% SF and 10% MK exhibited better mechanical behavior and a significant decrease in chloride penetration when compared to 10% FCC. It is noted that there was an increase in concrete carbonation when FCC or MK were used as additives. It was also observed that with longer curing time, the samples with and without additives, presented higher resistance to carbonation. The accelerated corrosion test by impressed voltage was also performed to verify the findings and to investigate the characteristics of corrosion using a 3.5% NaCl solution as electrolyte. The mixtures that contained 10% FCC were highly resistant to chloride ion penetration and did not present cracking within the testing period.